Adhesion, Microscopic, and Contact Test of Green Pesticides on Plants - Selfia Girsang; Johannes Situmorang; Ayu Amisa Fajrianti; Regina Fedora Elysia; Hesti Purwaningsih; Yura Witsqa Firmansyah (Jurnal Serambi Engineering, 2024)
The utilization of chemical pesticides will not be wholly absorbed by plants, resulting in the generation of residuals that are ultimately detrimental to the environment and public health. This research project was the impetus for the development of environmentally friendly pesticides. Its objective was to ascertain the adhesion of green pesticide formulations, their direct contact use, and the impact on plant microscopicity. This type of research is applied to the reformulation of green pesticides, with a particular focus on their adhesion and direct contact exposure to pests. This study employed a non-experimental design to elucidate the phenomenon of microscopic conditions in plants that had been sprayed with and without the use of green pesticides. The plant species utilized in this investigation were tomatoes, chilies, kale, and celery. The results of the green pesticide formulation, as determined by the stickiness of the pesticide in the good category, are reviewed based on the absence of pesticide droplets and the presence of a gloss on the morphology of the plant. Microscopic examinations revealed no discernible differences in the tomato, chili, and kale plants. However, the celery plants exhibited notable alterations, including the presence of chloroplast gaps and discoloration in specific regions, which were attributed to environmental factors (temperature) and the use of Span Tween. The tests demonstrated that the pesticide formulation is effective in repelling and killing the target pests, namely Plutella xylostella and Bemisia tabaci. It is imperative to develop formulations that will repel Aphis fabae and prevent damage to the leaf morphology of the plant.